2020
DOI: 10.1016/j.toxrep.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and repeated-dose toxicity evaluation of dried Wolffia globosa Mankai

Abstract: Highlights Wolffia globosa Mankai can serve as a plant substitute for animal protein. Genotoxicity and subchronic toxicity studies (GLP) of dry Mankai were conducted. Dry Mankai was judged as having no potential to induce gene mutations in Ames test. Dry Mankai did not induce chromosomal aberration in in vitro micronucleus test. The NOAEL of Dry Mankai in 90-day die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The authors evaluated genotoxicity and repeated-dose toxicity of dried W. globosa, introducing different percentages of dried plants to the diets of rats. The results showed no harmful effect attributable to supplementation with different doses of W. globosa to the rat diet [65]. Further studies aimed at testing the possible cytotoxic effect of duckweed on human cells concluded that none of the duckweed extracts from five analysed genera (including Wolffia) possessed any detectable anti-proliferative or cytotoxic effect [66].…”
Section: Human Nutritionmentioning
confidence: 91%
“…The authors evaluated genotoxicity and repeated-dose toxicity of dried W. globosa, introducing different percentages of dried plants to the diets of rats. The results showed no harmful effect attributable to supplementation with different doses of W. globosa to the rat diet [65]. Further studies aimed at testing the possible cytotoxic effect of duckweed on human cells concluded that none of the duckweed extracts from five analysed genera (including Wolffia) possessed any detectable anti-proliferative or cytotoxic effect [66].…”
Section: Human Nutritionmentioning
confidence: 91%
“…This NF application includes a request for protection of proprietary data in accordance with Article 26 of Regulation (EU) 2015/2283. The data requested by the applicant to be protected comprise: identification of plant material letter (Appenroth, 2014 ), in vivo determination of PDCAAS (Product Safety Labs, 2015 ), endophytic bacteria screening analyses, GRAS notification report (Ramboll Environ, 2015 ), bacterial reverse mutation test (Kawamata et al, 2020 ), in vitro mammalian cell micronucleus test (Kawamata et al, 2020 ), repeated dose 4‐day oral toxicity study (Pharmaseed Ltd, 2016 ‐unpublished), two repeated dose 28‐day oral toxicity studies (APS, 2018a ‐unpublished and APS, 2018b ‐unpublished), iron supplementation study in rats (Yaskolka Meir et al, 2019 ), 90‐day repeated dose oral toxicity study (non‐GLP) (NPHI, 2018 ‐unpublished), 90‐day repeated dose oral toxicity study (Kawamata et al, 2020 ).…”
Section: Data and Methodologiesmentioning
confidence: 99%
“…A 90‐day study (Study No. B‐8508) was performed in Sprague‐Dawley rats according to OECD 408 (2018) and in compliance to GLP standards (Kawamata et al, 2020 ‐confidential and proprietary). Animals were divided into four groups (10 animals/sex per group) and fed the NF at concentrations of 0%, 5%, 10% and 20% (w/w) in a powdered basal diet for 91 days (Lot #D20190407).…”
Section: Assessmentmentioning
confidence: 99%
“…Wolffia arrhiza and Wolffia globosa have been used as a protein replacement in feed for laying hens and quails (Chantiratikul et al, 2010a, b;Suppadit et al, 2012). Kawamata et al (2020) conducted toxicological studies on dried products of W. globosa (Dry Mankai). Dry Mankai was not genotoxic in a bacterial reverse mutation test and in vitro micronucleus assay.…”
Section: 7mentioning
confidence: 99%